Kerjasama Bilateral Indonesia dan Denmark dalam Pembangunan Pembangkit Listrik Tenaga Bayu (Studi Kasus: Pembangunan Pembangkit Listrik Tenaga Bayu untuk Keberlanjutan Energi di Sulawesi Selatan) - Sri Samhati; Alfian Hidayat; Mega Nisfa Makhroja (The Department of International Relations Universitas Mataram, 2023)
Energy demand from year to year has increased. Most of the energy used to meet this demand still comes from fossil fuels, meanwhile, the use of fossil fuels has an impact on increasing greenhouse gas (GHG) emissions. Therefore, Indonesia is trying to utilize renewable energy to reduce its use of fossil fuels. This study aims to determine the impact of bilateral cooperation between Indonesia and Denmark in the construction of a wind power plant (PLTB) on energy sustainability in South Sulawesi. This research uses the concept of Bilateral Cooperation and Energy Sustainability. The method used in this study is a descriptive qualitative approach and the technique of data collection is through literature study. This study concludes that the construction of PLTB with this cooperation has an impact on energy security in Indonesia, where there is fulfillment of energy demand, fulfillment of energy access, and reduction of fossil energy use.